2017
DOI: 10.1016/j.advwatres.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A numerical manifold method model for analyzing fully coupled hydro-mechanical processes in porous rock masses with discrete fractures

Abstract: In this study, a numerical manifold method (NMM) model was developed for fully coupled analysis of hydro-mechanical (HM) processes in porous rock masses with discrete fractures. Using an NMM two-cover-mesh system of mathematical and physical covers, fractures are conveniently discretized by dividing the mathematical cover along fracture traces to physical cover, resulting in a discontinuous model on a non-conforming mesh. In this model, discrete fracture deformation (e.g. open and slip) and fracture fluid flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Although some research has been initiated in recent years, particularly on the topic of pressure solution (Renard et al 1997;Yasuhara et al 2003Yasuhara et al , 2004Yasuhara et al , 2005Yasuhara and Elsworth 2008;Taron and Elsworth 2010), and on coupled processes in nuclear waste respositories or geothermal systems (Taron et al 2009;Gens et al 2010;Taron and Elsworth 2010;Zheng et al 2010;Rutqvist et al 2014;Rutqvist 2015Rutqvist , 2017, much remains to be done to advance the topic together with the multicomponent chemistry we typically consider be a centerpiece of modern reactive transport analysis. Most of the analyses to date have been based on continuum models, but there is a new interest in incorporating chemistry into discontinuum mechanics model that can track the evolution of deforming and reacting interfaces explicitly (Hu et al 2017).…”
Section: Chemical-mechanicalmentioning
confidence: 99%
“…Although some research has been initiated in recent years, particularly on the topic of pressure solution (Renard et al 1997;Yasuhara et al 2003Yasuhara et al , 2004Yasuhara et al , 2005Yasuhara and Elsworth 2008;Taron and Elsworth 2010), and on coupled processes in nuclear waste respositories or geothermal systems (Taron et al 2009;Gens et al 2010;Taron and Elsworth 2010;Zheng et al 2010;Rutqvist et al 2014;Rutqvist 2015Rutqvist , 2017, much remains to be done to advance the topic together with the multicomponent chemistry we typically consider be a centerpiece of modern reactive transport analysis. Most of the analyses to date have been based on continuum models, but there is a new interest in incorporating chemistry into discontinuum mechanics model that can track the evolution of deforming and reacting interfaces explicitly (Hu et al 2017).…”
Section: Chemical-mechanicalmentioning
confidence: 99%
“…Typical continuous approaches include the peridynamic method [15][16][17], the gradient damage method [18], and the phase-field method [19][20][21], to name a few. In addition, another type of methods combined the continuous and discontinuous methods, such as the combined finitediscrete element method [22], and the numerical manifold method [23][24][25][26]. These discrete and continuous methods or the combined approaches all have been applied for modeling of hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Wong employed NMM to investigate the effect of fracture flow on the stability of rock structure based on the HM model that treats the pore pressure as external traction on fracture faces. Recently, a model involving direct and indirect HM coupling analyses with the hydraulic head and displacement being primal variables was established for the rock masses with discrete and dominant fractures. However, it can be observed that these earlier NMM works seldom involve analysis of fully dynamic three‐field Biot model and the stability of NMM for locking phenomenon in poromechanics.…”
Section: Introductionmentioning
confidence: 99%